ANALISIS DAYA SAING DAN DAMPAK KEBIJAKAN PEMERINTAH TERHADAP PRODUKSI KAKAO DI JAWA TIMUR - Haryono, Dede; Soetriono, Soetriono; Hartadi, Rudi; Mulyo Aji, Joni Murti (Jurnal Sosial Ekonomi Pertanian, 2011)
This research is intended to: (a) know the trend resulting cocoa production of East Java province, (b) know the competitiveness of cocoa production (c) determine the impact of government policies on cocoa production, and (d) determine the effect of changes in input pricing policies on the competitiveness of cocoa output in East Java. The location of the research at PT. Perkebunan Durjo, district of Jember. The methods of research used are descriptive and analytical methods. The data was obtained through secondary data and primary data. The methods of analysis used are the production trend analysis and policy analysis matrix (PAM). The results showed that: (1) the development of cocoa production in East Java in 2016 is estimated to have increased by 46.97% from the year 2010, (2) the production of cocoa in East Java has competitiveness shown by the value of comparative advantage and competitive advantage, DRC value = 0.6148, PCR value = 0.7976, (3) government policies have a negative impact on cocoa production in East Java. This is indicated by NPCI = 1.2100, NPCO = 0.9587 and EPC = 0.8934 (4) policy changes in tradable input rate increases will reduce the competitiveness; changing DRC to be 0.621 and PCR to be 0.814.Key Words: cocoa, competitiveness, the impact of government policy